Entity Framework Core a full tour - Williams, Trevoir (Manning Publications, 2022)
In this course, Entity Framework Core - A Full Tour, you will learn to work with data in your .NET applications. Most times when courses are created for .NET technologies, the details of Entity Framework and its sheer power are neglected. We get distracted with abstractions and layers and don't focus on what Entity Framework is doing and can do. In this course, we will review the general benefits of using Entity Framework Core 5, which is Microsoft's flagship Object Relational Mapper (ORM), to relieve you of many concerns and challenges that come with this component of software development. We will also spend time discovering how EF Core translates classes and references to Database Models and Relationships. We will learn how to write queries, update databases incrementally, rollback changes and explore the myriad capabilities that Entity Framework Core affords us. When you're finished with this course, you'll have the skills and knowledge of Entity Framework Core needed to fluidly interact with data and write queries for .NET Core applications with ease.
Keywords: Microsoft .NET Framework; Streaming video; Internet videos; Database management; Vidéo en continu; Vidéos sur Internet; Bases de données; Gestion; streaming video